MHD convection in a square cavity with a heated cone: Effects of magnetic field and cone orientation (Journal of Bangladesh Academy of Sciences, 2023)
This paper presents a study on the influence of Magnetic Force impressed upon MHD fluid contained in a square cavity with a heated cone. The novelty of this work includes a heated cone whose orientation is varied at different angles. Calculations are performed for Prandtl number Pr = 0.71; Rayleigh number Ra = 10, 1000, and 100000; and Hartmann number Ha = 0, 50, and 100. The results are illustrated with streamlines, isotherms, and other relevant plots. It is observed that the influence of Ha becomes more noticeable with increasing Ra. Ha affects the flow by retarding the fluid movement and thus affects convective heat transfer. It is also observed that the cone orientation influences both fluid circulation and heat transfer. At high Ra, the vertical orientation of the cone resulted in lower heat flux than the left/right orientations. Also, under the same condition, the system remains cooler with the vertical cone at lower Ha, but becomes hotter after a certain value of Ha. These findings have practical design implications.J. Bangladesh Acad. Sci. 47(1); 127-137: June 2023